Аналіз ефективності методу кодування інформації на основі ортогонального перетворення Ґалуа - Превисокова, Н. В. (НТУ "ХПІ", 2016)
Пропонується метод кодування інформації на основі ортогонального перетворення в системах функцій Ґалуа. Визначено ефективність кодування на основі перетворення Ґалуа та здійснено порівняльний аналіз з іншими методами кодування на основі перетворень та методом імпульсно-кодової модуляції в задачах зменшення надлишковості інформації.

There have proposed method transform coding information on the Galois orthogonal functions base. A family of Galois orthogonal functions is formed and it is calculated orthogonal transform on this family base. The efficiency of Galois transform coding is calculated and comparative analysis with other transform coding methods and pulse code modulation is performed to solve the data compression problems.
Efficiency analysis of the method transform coding information on the Galois functions base
Keywords: кодування; система функцій Ґалуа; ортогональне перетворення; імпульсно-кодова модуляція; transform coding; Galois functions; orthogonal transform; pulse code modulation